Predicting anoxia in the wet and dry periods of tropical semiarid reservoirs. (15th January 2023) - Carneiro, Brenda Lara D.S.; de Jesus D Rocha, Maria; Barros, Mário U.G.; Paulino, Walt Disney; Lima Neto, Iran E.
Abstract: The dissolved oxygen (DO) level in the hypolimnion of lakes and reservoirs can reach anoxic conditions, which favor the release of phosphorus from the sediment bed to the water column. However, to estimate nutrient release from sediment is extremely important to quantify the duration of anoxia. In low latitude regions, the water-sediment layer is warmer than in temperate regions and eutrophication is usually more severe, potentially accelerating oxygen depletion and extending the anoxia period. Considering that the available equations to quantify the duration of anoxia were developed for temperate lakes, there is a need to effectively quantify this period in lakes and reservoirs located in other climate regions, such as the semiarid. In this study, the dynamics of thermal stratification was analyzed as a function of the Relative Water Column Stability coefficient (RWCS) and then correlated with DO dynamics for nineteen tropical semiarid reservoirs. RWCS values were higher during the rainy season, when anoxia duration was longer and the hypolimnion was thicker with respect to total water depth. Then, two new equations for quantification of anoxia duration, based on the equation originally developed for temperate climate, were adapted for the wet and dry seasons of the tropical semiarid region. The results showed that the proposed equations presented a better performance compared to the original one, which tends to underestimate anoxia in tropical semiarid reservoirs. This work intended to provide simple and locally adjusted tools to better quantify anoxic events and support the water quality and internal phosphorus load modeling for tropical semiarid reservoirs. Highlights: Combined methods were applied to assess anoxia in 19 tropical semiarid reservoirs. Dissolved oxygen dynamics was correlated with the relative water column stability. Anoxia in semiarid reservoirs is more intense and longer than in temperate ones. Severe and prolonged anoxic conditions occur during the wet season. Two new equations were proposed to predict anoxia in the wet and dry seasons.